COMPANY SIZE AND DIVIDEND POLICY ON THE FINANCIAL PERFORMANCE (JURNAL ECONOMICA : Research of Economic And Economic Education, 2023)
This study aims to identify and analyze effect of return on investment(ROI), cash ratio, earnings per share(EPS) and size for cash dividend of consumer goods companies listed in Indonesia Stock Exchange 2010-2014. The results showed that (1) return on investment and significant positive effect on cash dividends coefficient β 1.060688,value tcount 6.189669 sig value of 0.000 <0.05. (2) cash ratio is not positive and significant impact on the Company's cash dividend, the coefficient β 0.019816, tcount0.181014 and sign 0.8569 <0.05. (3) earnings per share positive and significant impact on cash dividends, the coefficient β 0.292543 . tcount6.845279 and sig 0.000> 0.05. (4) the size of the company and significant positive effect on cash dividends the coefficient β 0.826376 tcount12.57752 and Sig 0.000 <0.05. (5) F test results indicate the probability of an F-statistic obtained in cash dividends amounted to 0.000000 smaller than sig (0.05). Thus the variable return on investment, cash ratio, eaning per share and size perusahn jointly affect the cash dividend of consumer goods companies listed in Indonesia Stock Exchange 2020-2021